ANCA- associated vasculitis with pulmonary-renal syndrome in the elderly: a case report and review - Md Shah, Anim; Hashim, Uswaton Hasanah; Mohd Aris, Nur Alfalailah; Chai, Peng Ban; Sharif, Sherillia Affah; Peraba, Premila (Medical Journal Of Malaysia, 2024)
We present a case of a 67-year-old Chinese male who presented with acute kidney injury and nephrotic syndrome. The patient subsequently developed pulmonary hemorrhage, and his serum myeloperoxidase and proteinase 3 tests were positive, indicating ANCA-associated vasculitis. Due to the rapid progression of his clinical condition, treatment was initiated with plasma exchange and intravenous immunoglobulin, alongside induction therapy with high-dose glucocorticoids. Renal biopsy was not performed due to multiple challenges. During his two-month hospital stay, the patient required hemodialysis at least twice a week and received standard treatment of care. Despite the aggressive treatment approach, the patient continued to exhibit signs of renal insufficiency, necessitating ongoing supportive care and monitoring.